Revitalising Business Sustainability through Full-Range Leadership Approach: A Supply Chain Management View - Naharuddin, Nur Syahirah; Mohamad Mokhtar, Ahmad Rais (Information Management and Business Review, 2023)
The COVID-19 pandemic had a profound impact on small and medium enterprises (SMEs) worldwide, particularly those in emerging economies, disrupting their operations and affecting their sustainability. However, most SMEs were not able to utilize effective leadership to enhance their resilience and navigate the crisis successfully. This study aims to examine the relevance of the Full-Range Leadership Model in understanding the relationship between leadership styles and business sustainability, in the context of operations and supply chain management. The study used a cross-sectional survey approach with a purposive sampling technique to collect data from 214 SMEs in Malaysia. The findings of this study suggest that transformational and transactional leadership styles are significant and positive factors that contribute to business sustainability. On the other hand, laissez-faire leadership is a significant and negative factor that hinders the development of business sustainability and resilience. Therefore, SMEs should incorporate and leverage different leadership styles to strengthen their resilience in the post-pandemic work economy. This study has important implications for SMEs to improve their sustainability and resilience in the face of future crises. By adopting effective leadership styles, SMEs can improve their resilience, build their capacity to adapt to changes and enhance their long-term sustainability